Feasibility study of new functions in ancient urban context in Shah Abbasi of Karaj - kyarash ardestanipourhazhir (تحقیقات کاربردی علوم جغرافیایی)
The city is a vibrant and dynamic creature whose body is shaped at different times by natural and social economic, political, cultural and economic developments. In a sound and healthy fashion, these developments are such that the old elements of the cities are restored to meet the new needs. In the structure and even in the destruction of these tissues. The purpose of this study was to investigate the feasibility of creating new functions in ancient urban context. The present study is of applied purpose and of descriptive-analytical method. The statistical population of the study was comprised of experts in the field of research and the sample size was 30 persons. The results of the implementation of the Suara model showed that among the indicators identified for the social dimension, the role of owner-investor participation index with a final score of 0.224 was ranked first, for the economic dimension, the index of participation in purchase and construction and Builder in the range with a final score of 0.306 in the first rank, for the physical dimension Paying attention to meet the current needs for physical and functional change with a score of 0.416 in the first rank, and for the environmental dimension Indicator Role of New Construction in the Area Infrastructure With a score of 0.610, it is the highest.